Peptic Duodenal Stricture Causing Gastric Outlet Obstruction: A Case Report - Kurniawan, Andree; Tan, Christine (The Indonesian Society for Digestive Endoscopy, 2023)
Gastric outlet obstruction (GOO) is an uncommon but serious problem caused by benign causes. The incidence of GOO caused by peptic ulcer disease (PUD) is decreasing due to successful Helicobacter pylori treatment. Hence, these aggressive cases are rare. We present a case of a man who experienced intermittent abdominal pain and constipation for a week but acutely worsened in the last five days. He complained of intractable nausea and vomiting, leading to intolerable oral intake. Physical examination revealed abdominal distention, tenderness in epigastrium and right hypochondrium, and hypoactive bowel sounds. Laboratory results revealed leukocytosis with neutrophilia. Gastroscopy showed erosive esophagitis, pangastritis, and large duodenal ulcer causing stricture of duodenum pars I. An open distal gastrectomy, Roux-en-Y reconstruction, and fundoplication was then performed. The patient’s general condition improved after ninth day of care and was discharge on the eleventh day of care. PUD is a major cause of GOO, but incidence has decreased to 5% with the use of proton pump inhibitors. If the distal stomach or duodenum is significantly obstructed, GOO should be considered. The gold standard for diagnosis is endoscopy. Initially, conservative and supportive therapy should be done followed by endoscopic treatment in appropriate cases. If there is no improvement, surgical interventions should be done. This case demonstrated the need for definitive invasive procedures in the intervention of GOO caused by PUD. When conservative measures fail, this case also adds support to the direct anatomic treatment of duodenal strictures.